Teachers Effort In Building The Qurani Soul In Students - Fitri lestari; Nur aini nindra utami (Proceeding International Seminar of Islamic Studies, 2019)
Research titled the efforts of teachers in building the qurani soul in students. The problem that arises is that many students are less able to build a qurani soul in themselves. Do students not have a qurani soul so teachers must build a qurani in themselves students. The purpose of this studi is to build the soul of the quran in students. The method used is library research,and qualitative. It was found that in building the soul of the qurani in the students it varied according to the needs of the students.